ENVIRONMENTAL SENSITIVITY INDEX FOR OIL SPILLS IN COLOMBIAN RIVERS (ESI-R): APPLICATION FOR THE MAGDALENA RIVER - Diego L Gil-Agudelo (CT&F Ciencia, Tecnología y Futuro, 2019)
The Environmental Sensitivity Index (ESI) mapping has been used globally for oil spill planning and response purposes in coastal areas since its development in the 1970s. However, application to riverine habitats has been limited. Following US National Oceanic and Atmospheric Administration (NOAA) formats and adapting them in working sessions held by a multidisciplinary team and in special sessions with experts and consultants in Colombia, this paper describes the development and application of the sensitivity index to develop maps for the conditions of the middle Magdalena River in Colombia. The index developed (ESI-R) is useful for application in other major rivers in Colombia and areas with similar characteristics. The use of the index to develop maps for smaller rivers and streams is likely to require further development.